A relação do processamento visual e processamento temporal em crianças com dificuldade de leitura e escrita - Fiore, Adriana dos Santos (2019)
Among the main learning difficulties, the best known to parents and teachers are those related to academic performance, such as understanding the spoken word, reading, writing and logical reasoning. Because reading is a multisensory activity, several factors can lead to such difficulties, such as changes in visual processing and auditory processing. Considering hearing and vision the main ways of access to information and therefore learning, we see the importance of studying these skills for better therapeutic and pedagogical intervention. Objective: To investigate the relationship between visual processing and temporal processing in children with reading and writing difficulties. Method: Observational and cross-sectional clinical study with 123 children without hearing loss, all 10 years of age, divided into study group and control group, regularly enrolled in the 5th. Year of Primary Education. For evaluation, the following tests were used: Frequency Pattern Test (PPS), Dictation Digit Test (TDD), Random Interval Detection Test (RGDT) and Visual Reading Perception Scale (EPVL). Results: Schoolchildren of both groups presented considerably better performance in TDD in the task of binaural separation, both in O.D., as much as, in the OE when compared to the integration condition. RGDT was the least noticed test altered in both groups. Study group presented worse performance in the PPS test and also greater discomfort and reading difficulty when compared to the experimental group. Conclusions: In the present study, binaural integration and separation abilities, as well as temporal ordering and resolution abilities were associated with reading difficulties and discomfort, but the use of colored spectral overlays did not bring significant gains to schoolchildren during reading